PENGARUH TEKANAN FUEL PUMP DAN JUMLAH LUBANG INJECTOR TERHADAP PERFORMA MOTOR 150CC: EFFECT OF FUEL PUMP PRESSURE AND NUMBER OF INJECTOR HOLES ON 150CC MOTOR PERFORMANCE - Fian Arif Yulianto (Jurnal Teknik Mesin, 2024)
This study examines the effect of fuel pump pressure and the number of injector holes on the performance of the Honda Vario 150cc motorbike. The current fuel system has evolved from a carburetor to an injection system to improve fuel efficiency. The injector plays a role in spraying fuel into the combustion chamber with the volume and discharge set by the ECU. This study aims to improve and compare engine performance with variations in the number of holes in the injectors and fuel pump pressure.The research method used is experimentation by measuring the power and torque of the engine. The results showed that the number of injector holes and fuel pump pressure had an influence on the power and torque of the motorcycle. The increased number of holes increases the power and torque potential. Increasing the fuel pump pressure also improves engine performance.At the top speed, the best combination is found in the fuel pump pressure of 2.5 bar with 6-hole injectors. The optimal combination of the number of holes and fuel pump pressure can increase the power and torque of the motor